Experimental investigation of a model bulb turbine under steady state and load rejection process. (May 2021) - Chen, Huixiang; Zhou, Daqing; Kan, Kan; Xu, Hui; Zheng, Yuan; Binama, Maxime; Xu, Zhe; Feng, Jiangang
Abstract: With the advantages of large flow capacity, low head, and high efficiency, the tubular turbine can well meet the demand for renewable resources. To obtain its synthetic characteristics in full operating conditions, model tests on both the steady state and transient process were designed and conducted in an ultra-low head bulb turbine. The similitude criteria, model test system, and test method were introduced; experiments on comprehensive steady-state and load-rejection conditions were performed; and the results were analyzed. Based on the steady-state test, the variation of flow, torque, and axial force with respect to the rotating speed, runner blade (RB) opening, and guide vane (GV) opening were revealed. Dynamic test results showed that the closing laws of GV and RB have an obvious influence on the quality of the transient process. Orthogonal optimization was used to acquire the optimal closing scheme of GVs and RBs when the turbine undergoes full load rejection under rated head conditions. Our test results provide a sound reference for the design and operation of tubular turbine units. Highlights: The synthetic performance of a double regulated bulb turbine was experimentally studied. The characteristics of three key parameters in steady state were revealed and analyzed. The external variation of different hydraulic parameters were explored and deeply analyzed. The optimal closing scheme of regulating mechanism was acquired by using orthogonal optimization method.